PENGEMBANGAN BAHAN AJAR PEMBELAJARAN SAINS BERBASIS REKAYASA UNTUK PENDIDIKAN ANAK USIA DINI (PAUD) DI PAUD NEGERI PEMBINA 2 KOTA TEBING TINGGI - Supartik Supartik; Anita Yus; Deny Setiawan (JURNAL TEMATIK, 2019)
This study aims to develop butterfly metemorposa teaching materials andPAUD children's activity sheets. This type of research is research and development usingthe van den akker model. The results of this study indicate that the validation of textbooksand children's activities is very good and the children's understanding of butterflymetamorphosis teaching material has increased. This can be seen through initial tests andfinal tests. in the initial test of the country of Trustees 2 there were 22 children or 62.85%in the sufficient category. After the initial test carried out computer-assisted engineeringlearning and using textbooks and child activity sheets developed by researchers, the finaltest results obtained by the Trustees 2 Public PAUD were 25 or 71.42% of children or665.72% and Pembina 3 PAUD of 25 children or 78.13% fulfill the permendiknamandate 58 of 2009, from this result there is an increase for PAUD Pembina 2 by 30%while Negeri Pembina 3 PAUD increases by 35%. So that the impact of using textbooksand child activity sheets and computer-assisted engineering learning can improvechildren's learning outcomes.